2017
DOI: 10.1097/htr.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Traumatic Brain Injury and Criminality in Juvenile Offenders

Abstract: The high rates of TBI and levels of distress found in juvenile offenders suggest a need for preventive actions, interventions to compensate for challenges related to TBI, and programs to assist individuals' transitions into the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Nine of the twelve studies investigated adults in prison and three, juveniles in prison (27)(28)(29). One was a national prison population study that included adults and juveniles (4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine of the twelve studies investigated adults in prison and three, juveniles in prison (27)(28)(29). One was a national prison population study that included adults and juveniles (4).…”
Section: Resultsmentioning
confidence: 99%
“…There was high risk of bias in all but one study where the sample size was modest (n=38) and the prevalence of HI (by self-report) the highest of all studies (95%) (32). Studies on juvenile females report a prevalence of 28%-49%, with one study reporting a prevalence of HI with LoC of 49% (27)(28)(29). Overall fewer than half of the studies (28,29,32,34) reported severity of HI using internationally recommended definitions (35) and only four studies (24/25, 27, 32, 33) used a HI screening tool that is validated for a prison population.…”
Section: Methods For Assessing the Prevalence Of Hi In Female Offendersmentioning
confidence: 95%
See 2 more Smart Citations
“…A section of BISQ is an inventory of 100 four-point-rated symptoms that characterize a comprehensive range of transient and chronic problems after brain injury. A factor analysis of these symptoms revealed four main factors ( 42 ), which were labeled as memory-attention, depression-anxiety-mood, aggression-impulsivity, and physical. Symptom factor scores are scaled from 0 to 3, with 0 indicating no symptoms.…”
Section: Methodsmentioning
confidence: 99%